The e-Government adoption in Higher Education in Portugal: The case of ISCSP at Lisbon University - Monteiro, Maria Helena; Ramos Pinto, Ricardo (Journal of Information Systems and Technology Management, 2019)
Was studied the adoption of information technologies in the higher education area in Portugal, analysing the case of a centenary institution (ISCSP) and trying to understand how its leadership managed and organized the ICT capabilities to deliver value to students, professors and all other stakeholders. Innovative ICT capabilities were introduced within a planned, motivated and controlled environment where leadership styles and management practices were always focused on business success. We applied a Program Transformation Model based in good practices of Policy Research innovation and diffusion Models complemented with Program Management approaches. Through the academic results and data obtained during this program’s implementation we present experience evidence that confirms the progressive Digital Transformation of the ISCSP at Lisbon University.